Extended Abstracts of the 2014 International Conference on Solid State Devices and Materials 2014
DOI: 10.7567/ssdm.2014.c-6-2
|View full text |Cite
|
Sign up to set email alerts
|

A New Classification of Nano-Scale Crystallinity of In-Ga-Zn-Oxide Films

Abstract: We have reported that, in semiconductor devices based on In-Ga-Zn-O (IGZO), the crystallinity of IGZO is associated with the reliability of the devices. Therefore, evaluation and classification of the crystallinity is important. In this study, we evaluated nano-scale crystallinity of IGZO films deposited by various conditions, and found the relationship between nano-scale crystallinity and physical properties related to the reliability, so that we propose a new classification of the crystallinity of IGZO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
1
1
Order By: Relevance
“…We tried to reproduce an a-IGZO film reported by Kamiya, Hosono, and others by using magnetron sputtering and PLD; however, we were not able to confirm the existence of a completely amorphous structure. We cannot yet confirm effects and features caused only by an amorphous morphology, which are presented in many papers by Hosono and others, including papers by Nomura et al 3,18,19 We found that nanocrystals exist in a-like IGZO that is close to the amorphous morphology. Furthermore, the electron energy from electron-beam irradiation changes the crystalline structure of the a-like IGZO film.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…We tried to reproduce an a-IGZO film reported by Kamiya, Hosono, and others by using magnetron sputtering and PLD; however, we were not able to confirm the existence of a completely amorphous structure. We cannot yet confirm effects and features caused only by an amorphous morphology, which are presented in many papers by Hosono and others, including papers by Nomura et al 3,18,19 We found that nanocrystals exist in a-like IGZO that is close to the amorphous morphology. Furthermore, the electron energy from electron-beam irradiation changes the crystalline structure of the a-like IGZO film.…”
Section: Discussioncontrasting
confidence: 56%
“…3,18 Therefore, we applied the PLD method to form an IGZO thin film and evaluated the film quality. 19 IGZO films were formed by the PLD method with a Nd:YAG laser (λ = 266 nm, 10 Hz repetition frequency, 0.1 W), using a Result and discussion.-Figure 9 shows cross-sectional TEM images and NBED patterns of the IGZO films formed under the above pressures. Crystal grains having different sizes ranging from several nanometers to several tens of nanometers were observed in the films deposited at 2.6 × 10 −5 Pa and 1 × 10 −3 Pa.…”
Section: Characteristics Of Igzo Thin Films Formed By Pulsed Laser De...mentioning
confidence: 99%